A study of the development of higher education in the Bahamas and its relationship to national goals - Massiah, Erna (1979)
This study sought to identify factors responsible for the development of higher education and national goals in the Bahamas, and to investigate whether higher education programmes and courses introduced since 1973 supported national goals for education. The objectives were to: (a) provide an historical overview of the Bahamas from 1492 to 1973, focusing on the development of primary and secondary education; (b) trace the organization of higher education from 1947 through the colonial era, and survey its development and administration from 1973 to 1977; and (c) show how goals in the "Five Year Plan" for higher education supported national goals. Data were collected from documentary research and interviews with selected persons. It was found that: 1) early colonial education had recorded slow progress due to the government's inconsistent policy and sporadic provisions of educational services. Changes since 1967 in political and economic spheres had reflected improved educational planning and steady progress; 2) agencies adhering to British traditions had provided higher education in the colonial era, which had greatly influenced Bahamian education. Changes in philosophy and approach were evidenced in the post-Independence administration of higher education; and 3) most of the data supported national goal achievement, thus supporting the assumption that there was a relationship between higher education and national goals; Bahamian national goals had influenced the development of higher education goals
Keywords: History of education